Performance Appraisal of Fresh Milk Supplier using Analytic Network Process Method and Rating Scale: Case Study in ‘Pusat Koperasi Industri Susu’ Sekar Tanjung Pasuruan - Arin, Riska Devi Nur; Astuti, Retno; Ikasari, Dhita Morita (Jurnal Teknologi Pertanian, 2013)
Pusat Koperasi Industri Susu (PKIS) Sekar Tanjung Pasuruan is a company engaged in the processing of milk. Performance improvement is needed in increasing competitiveness of PKIS Sekar Tanjung Pasuruan. One of the factors that affect the performance of PKIS Sekar Tanjung Pasuruan is performance of its suppliers. The purposes of this research were to obtain the weight of fresh milk supplier performance criteria by applying Analytic Network Process (ANP) method and to get the order or priority of fresh milk supplier based on rating scale. ANP is a weighting performance criteria method. ANP involves the interaction and dependence of high-level elements in the hierarchy of low-level elements. By using ANP method, supplier performance was expected being able to be assessed in accordance with the company’s key criteria. The result of criteria weight were efficiency (0.088), flexibility (0.056), responsiveness (0.503), and food quality (0.353). The result of subcriteria weight were production cost (0.044), transaction cost (0.044), consumer satisfaction (0.008), volume flexibilities (0.019), delivery flexibilities (0.003), delivery delay (0.026), fill rate of order quantity (0.143), suitable of delivery method (0.260), consumer complain (0.100), physical appearance (0.024), safety and healthy product (0.042), product reliability (0.059), production system (0.189), and environmental aspect (0.039). The results of performance assessment of fresh milk supplier based on descending scores are supplier F (3.331), supplier A (3.213), supplier D (2.917), supplier C (2.875), supplier E (2.722), and supplier B (2.672).Key Words: ANP,  Rating Scale, performance of supplier